THE SuperTIGER Instrument: Measurement of Elemental Abundances of Ultra-Heavy Galactic Cosmic Rays - Daniels, W. M.; Mitchell, J. W.; Stone, E. C.; Binns, W. R.; Braun, D. L.; Murphy, R. P.; Mewaldt, R. A.; Hahne, D. J.; Brandt, T. J.; Israel, M. H.; Klemic, J.; Wiedenbeck, M. E.; et al. (2014)
The SuperTIGER (Super Trans-Iron Galactic Element Recorder) instrument was developed to measure the abundances of galactic cosmic-ray elements from Ne-10 to Zr-40 with individual element resolution and the high statistics needed to test models of cosmic-ray origins. SuperTIGER also makes exploratory measurements of the abundances of elements with 40 < Z < or = 60 and measures the energy spectra of the more abundant elements for Z < or = 30 from about 0.8 to 10 GeV/nucleon. This instrument is an enlarged and higher resolution version of the earlier TIGER instrument. It was designed to provide the largest geometric acceptance possible and to reach as high an altitude as possible, flying on a standard long-duration 1.11 million cu m balloon. SuperTIGER was launched from Williams Field, McMurdo Station, Antarctica, on 2012 December 8, and made about 2.7 revolutions around the South Pole in 55 days of flight, returning data on over 50 x 10(exp 6) cosmic-ray nuclei with Z > or = 10, including approx.1300 with Z > 29 and approx.60 with Z > 49. Here, we describe the instrument, the methods of charge identification employed, the SuperTIGER balloon flight, and the instrument performance.